Surface and sub-surface mycoflora of jute (Corchorus olitorius and C. capsularis) - N. BEHERA, A.K. SAHU and (Indian Phytopathology, 2002)
The surface and sub-surface fungal flora of 12 varieties of jute (C. olitorius and C. capsularis) were studied using 4 different techniques. The blotter method and seed inoculation in agar provided a complete picture of the seed coat fungi, while the surface sterilization technique gave information on endophytic fungi. A total of 57 ectophytes and 5 endophytes were isolated. A greater number of c.f.u. were recorded on C. olitorius than on C. capsularis. Of the seed coat fungi, Aspergillus was the dominant species followed by Penicillium. The endophytes recorded were Macrophomina phaseolina, Fusarium oxysporum, F. moniliforme [G. fujikuroi] and Sclerotium rolfsii [Corticium rolfsii].